A coal-sulfur model for Sydney Coalfield (Upper Carboniferous), Nova Scotia, Canada - Zodrow, Erwin (Atlantic Geology, 1991)
Methods of modern factor analysis are applied to a set of 31 variables (metals, sulfur and ash) of coal data, with focus on explaining the sulfur variance in coal for the formulation of a coal-sulfur model. The derived five hypothetical factors which are fitted lo the conceptual coal-sulfur model are inferred to represent general sedimentary/ geochemical processes, except for one for which there is no available identity and no corresponding process in the conceptual model. The fluvial sedimentary influx and the pyrite-forming factors are the most influential in explaining the variation of sulfur in the coal, where the latter factors are linked with sulfur supplied from recycled sulfate solution. The factor interpretation is consistent with independent results that identify clay minerals and pyrite as the dominating coal mineralogy in the Sydney Coalfield.